Primary care for the urban poor in India during the pandemic: Uninterrupted management of non-communicable diseases and home-based care of patients with COVID-19 infection - Abraham, Sunil; John, Sushil Mathew; Gupta, Archna; Biswas, Seema; Khare, Manorama M.; Mukherjee, Pavan; Frankline, Augustine C. (Frontiers in Public Health, 2023)
The two waves of COVID-19 severely affected the healthcare system in India. The government responded to the first wave with a strict nationwide lockdown which disrupted primary care, including the management of non-communicable diseases (NCDs). The second wave overwhelmed healthcare facilities resulting in unavailability of beds and inadequate access to hospital services. Collectively, these issues required urgent responses including adaptation of primary care. The Low Cost Effective Care Unit (LCECU), a 48-bed unit of the Department of Family Medicine of Christian Medical College, Vellore (CMC) was started in 1982 to care for the poor of Vellore town. It has been actively working among the urban communities from 2002, with a focus on Community Oriented Primary Care among six urban poor communities since 2016. In addition to the outpatient and in-patient services, LCECU has a network of community volunteers, community health workers, an outreach nurse, social workers and doctors who operate clinics in poorer areas of Vellore. During the first wave the network adapted quickly and ensured that patients with NCDs had uninterrupted care and supply of medicines by visiting them in their homes. A daily lunch service was organised in the communities for 600 people for more than 2 months. During the second wave the unit responded quickly to the lack of hospital services by organizing and delivering home based care to monitor patients affected by COVID-19. A system was developed in collaboration with other CMC departments and implemented with the active collaboration of the communities to provide this.